Molecular Heterogeneity in Neuroblastoma and Its Clinical Significance - Tekincan Çağrı Aktaş; Safiye Aktaş; Efe Özgür Serinan; Pınar Erçetin; Melek Aydın; Özde Elif Gökbayrak; Aylin Erol; Zekiye Altun; Nur Olgun (Galenos Publishing House, 2023)
Objective: Tumor heterogeneity describes the differences between cancer cells in the same tumor sample. Neuroblastoma (NB) is a type of cancer where tumor heterogeneity complicates its treatment. This study aims to explore the role of molecular heterogeneity detected by routine molecular tests in NB. Method: Seventy-one patients were included in the study. NB samples were chosen among 1,300 NB samples that were evaluated using molecular tests between 2012-2020 according to the guidelines of Turkish Pediatric Oncology Group Protocol. Molecular investigations were performed (total 142 samples) obtained from two different areas of the tumor (synchronous) or at two different times (metachronous). Heterogeneity was questioned for five tests: MYCN amplification, 1p36LOH, 11q23 deletion and 17q25 gain (identified with real-time polymerase chain reaction) and DNA ploidy (identified with flow cytometry). Results: Heterogeneity was observed for MYCN in 22.53%, for 1p36LOH in 36.62%, for 11q23del in 29.58%, and for 17q25 gain in 40.85% of cases, while DNA ploidy was heterogeneous in 36.4% of cases. Molecular heterogeneity did not show statistical difference among metachronous and synchronous cases. High-risk cases more frequently displayed molecular heterogeneity without any statistically significant difference between both groups. Conclusions: Our findings support the fact that molecular heterogeneity either exists in different areas of a tumor or seen in the same tumor at different times. It will be beneficial to perform more than one molecular analysis on the tumor tissue specimens. In addition, recurrences or re-biopsy specimens from metachronous metastases shall be re-evaluated using molecular tests in cases of NB.